Bioactive Peptides from Velvet Bean Tempe: Neutrase-Catalyzed Production in Membrane Reactor - Azis Boing Sitanggang; Tsaniyah Ayu Mauliasyam; Nadine Kurniadi; Slamet Budijanto; Ho-Shing Wu (Jurnal Teknologi dan Industri Pangan, 2023)
Velvet beans are potential sources of parent proteins for bioactive peptide production. In this study, a combination of fermentation and neutrase-catalyzed continuous hydrolysis in an enzymatic membrane reactor was performed to produce antioxidative and angiotensin I-converting enzyme inhibitory (ACEi) peptides. The optimum operating conditions were τ = 6 h and [E]/[S] = 7.5%. The resulting permeate, which was a<10-kDa fraction, exhibited antioxidant activity at 0.38 mg ascorbic acid equivalent antioxidant capacity (AEAC)/mL (2,2-diphenyl-1-picrylhydrazyl, DPPH inhibition) and 0.26 mg AEAC/mL (ferric reducing antioxidant power, FRAP), and ACEi activity of 81.02%. Further fractionation of the permeate increased the ACEi activity in which 2-kDa fraction showed the most potent activity (IC50 = 0.23 µg protein/mL). The IC50 value of the outcome was comparable to those reported in the literature for velvet bean-based peptides. Furthermore, this study suggests that neutrase is a good catalyst candidate for the synthesis of bioactive peptides from velvet beans.